Caregiver burden as a predictor of depression among family and friends who provide care for persons with bipolar disorder. (23rd March 2016) - Perlick, Deborah A; Berk, Lesley; Kaczynski, Richard; Gonzalez, Jodi; Link, Bruce; Dixon, Lisa; Grier, Savannah; Miklowitz, David J
Abstract : Objectives: Over one‐third of caregivers of people with bipolar disorder report clinically significant levels of depressive symptoms. This study examined the causal relationship between depression and caregiver burden in a large sample of caregivers of adult patients with bipolar disorder. Methods: Participants were 500 primary caregivers of persons with bipolar disorder enrolled in the Systematic Treatment Enhancement Program for Bipolar Disorder (STEP‐BD).This study evaluates the strength and direction of the associations between caregiver burden and depressive symptoms at baseline and at six‐ and 12‐month follow‐up using cross‐lagged panel analyses, controlling for the clinical status of patients and sociodemographic variables. Results: Higher levels of overall caregiver burden at baseline were associated with increased levels of depressive symptoms among caregivers at follow‐up ( F = 8.70, df = 1, 290, p < 0.001), after controlling for baseline caregiver depression, gender, race, age, social support, and patients' clinical status. By contrast, caregiver depression at baseline was not significantly associated with caregiver burden at follow‐up ( F = 1.65, p = 0.20). Conclusions: Caregiver burden is a stronger predictor of caregiver depressive symptoms over time than the reverse. Interventions that help alleviate caregiver burden may decrease depressive symptoms.